Does Employment Status Affect Breastfeeding? - Lina Handayani; Azlina binti Mohd Kosnin; Yeo Kee Jiar (International Journal of Evaluation and Research in Education (IJERE), 2013)
The infant feeding decision is complex and involves the influence of psychological, social, and economic factors, and health care system. For working mothers, there are more obstacles and barrier for practicing breastfeeding successfully. Successful breastfeeding for working mothers is not a simple matter.DOI: http://dx.doi.org/10.11591/ijere.v2i4.3126